Effectiveness of Helped Mathematical Learning Media of Lectora Inspire on The Number Sense Ability of Fifth Grade Students of Elementary School in Substrate Materials - Frida Marta Argareta Simorangkir; Ribka Kariani Br Sembiring (Budapest International Research and Critics University, 2018)
The purpose of this study was to determine the effectiveness of Lectora Inspire assisted mathematics learning media on the number sense ability of elementary school fifth grade students. This research is a development research using 4-D design that is Define, Design, Develop and Disseminate or adapted to 4-D model that is defining, designing, developing and distributing. The test sample was the fifth grade students of Medan Kartika I-2 Private Elementary School. Products developed after being declared valid by experts / experts, then tested. Product validation results are stated to be very valid. Based on the results of the validation of learning materials by 93.82%, instructional design by 91.03%, media experts on Lectora Inspire by 87.5%, student responses to Lectora Inspire amounted to 95.57% and the teacher's response to the Lectora Inspire amounted to 89.56 % in very good category. Based on the average value of the data gain the ability of the student's number sense is 0.70 in the high category. Increased ability of student number sense is 0.27. From the results of the analysis, it can be stated that by using Lectora Inspire assisted mathematics learning media in learning related to fractional materials can increase the number sense ability of students.